1990
DOI: 10.1007/bf02390859
|View full text |Cite
|
Sign up to set email alerts
|

Findings in 200 consecutive asymptomatic women, having a laparoscopic sterilization

Abstract: Laparoscopic findings in 200 asymptomatic, healthy women having a sterilization were recorded; 148 patients (74%) had no abnormality and 52 patients had abnormalities comprising pelvic adhesions (14%), uterine fibromyomas (5%), endometriosis (3%) and ovarian or parovarian cysts (2%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Trimbos recorded laparoscopic findings in 200 asymptomatic women having a sterilization. In 26% of these women, abnormalities were found including 14 of pelvic adhesions [16]. Rapkin found a percentage of 39% adhesions with laparoscopy of which 12% showed CPP.…”
Section: Laparoscopymentioning
confidence: 97%
“…Trimbos recorded laparoscopic findings in 200 asymptomatic women having a sterilization. In 26% of these women, abnormalities were found including 14 of pelvic adhesions [16]. Rapkin found a percentage of 39% adhesions with laparoscopy of which 12% showed CPP.…”
Section: Laparoscopymentioning
confidence: 97%
“…Trimbos et al found 14% pelvic adhesions in women undergoing laparoscopic sterilisation. 20 Adhesions are often found in women without pain: Stovall et al found 49% adhesions in patients with CPP and in 34% of controls without CPP. 25% of patients with adhesions experienced no pain at all.…”
Section: Relation With Cppmentioning
confidence: 98%
“…19 Nevertheless, pathology is also reported in patients without CPP: Trimbos et al found 26% of pathology in asymptomatic women, Stovall et al reported pathology in 29% and Howard in 28% of patients without CPP. 10,20,21 In a review Howard concluded that 61% of patients with CPP had a pathological condition on laparoscopy. He showed that less than 50% of women with CPP were helped by diagnostic and operative laparoscopy.…”
Section: Diagnosismentioning
confidence: 99%
“…27 Though adhesions may play an etiologic role in chronic pelvic and/or abdominal pain, they do not always produce pain. Adhesions may be more likely to play an etiologic role when they limit the mobility of intra-peritoneal organs or when their location correlates with the location of the pain.…”
Section: Pelvic Adhesive Diseasementioning
confidence: 99%